A lipid-soluble extract of Pinellia pedatisecta Schott orchestrates intratumoral dendritic cell-driven immune activation through SOCS1 signaling in cervical cancer. (1st March 2021) - Wang, Yumeng; Lu, Chong; Huang, Haixia; Yao, Sheng; Xu, Congjian; Ye, Yang; Gui, Suiqi; Li, Guiling
Abstract: Ethnopharmacological relevance: Pinellia pedatisecta Schott extract (PE) is generated from Pinellia pedatisecta Schott, a traditional Chinese medicinal plant. PE suppresses cervical tumor growth and exhibits effects on dendritic cells (DCs) that lead to modulation of antitumor CD4 + and CD8 + responses. Aims: To explore the underlying mechanisms by which PE modulates tumor-associated dendritic cell (TADC) activation and function. Methods: DCs and TADCs were generated from murine bone marrow and exposed to PE solutions at different doses, as well as to repeated doses separated at different time intervals. Quantitative PCR, Western blot analysis, flow cytometry, and gene silencing were used to analyze the modulatory effects of PE on the SOCS1/JAK2/STAT pathways. Furthermore, we separated human cervical tumor-infiltrated DCs (TIDCs) and conducted an ex-vivo stimulation model to observe the effect of PE. For phenotypic analysis of cultured DCs and ex vivo human specimens, we used flow cytometry to detect the molecular markers associated with cell function. Results: In cultured TADCs and human cervical TIDCs, maturation- and functional markers (MHCII, CD80, CD83, CD86, and IL-12) were downregulated, whereas SOCS1 was upregulated. PE enhanced the expression of CD80, CD86, and IL-12 in cervical TIDCs, which induced increased expression of CD107a, GZMB, and perforin in CTLs, and furthermore induced apoptosis in a larger number of tumor cells. In cultured TADCs, PE downregulated SOCS1 expression and activated the phosphorylation of JAK2, STAT1, STAT4, and STAT5 in both dose- and time-dependent manners. The effects of PE upregulating MHCII, CD80, CD86, IL-12 on TADCs were blocked after SOCS1 silencing. Conclusions: In this study, PE restored the impaired function of cervical TIDCs, thereby eliciting further antitumor CTL responses. The effects of PE on TADCs were mediated through inhibition of SOCS1 and activation of downstream JAK2-STAT1/STAT4/STAT5 pathways. PE may be a potent and effective immunomodulatory drug for antitumor treatment via the blockade of SOCS1 signaling in DCs. Graphical abstract: Image 1 Highlights: Human cervical cancer infiltrated dendritic cells exhibited dampened activating phenotype and SOCS1 hyperexpression. PE restored the impaired function of cervical cancer infiltrated dendritic cells and enhanced antitumor T cell responses. The effects of PE are mediated through inhibition of SOCS1 and activation of downstream JAK/STAT signalling.